Ethnic residential patterns in the inner-city core of Riga, Latvia using scalable individualized neighborhoods - Balode, Sindija; Bērziņš, Māris (Frontiers in Sustainable Cities, 2025)
Urban residential segregation of immigrant populations is a key research area. Riga, Latvia, offers a unique context due to its Soviet-era migration legacy and increasing diversity from new immigration flows amidst demographic decline of established minorities. Analyzing the spatial patterns of emerging ethnic groups, who often exhibit residential clustering, is key to understanding potential spatial inequalities. This study investigated the residential concentration, isolation, and segregation of emerging ethnic groups in Riga's inner-city core using a multi-scalar geographic approach. Analyzing anonymized individual-level 2021 census data processed with EquiPop, we found that residential distribution and concentration varies significantly by spatial scale. Individualized neighborhoods effectively revealed multi-scalar patterns and intra-neighborhood heterogeneity. Results identified a concentration of new ethnic groups in the southern inner-city core, functioning as an “arrival space”, alongside an influence of existing ethnic infrastructure on shaping residential patterns. This research provides crucial insights into the fine-scale spatial organization of new immigrant communities, informing the understanding and addressing of spatial inequalities, particularly those faced by non-European groups within the complex European context.